Manajemen Dakriosistitis - Salsanisa Tisno Nurladira (Yayasan Pendidikan Medika Indonesia, 2021)
Dacryocystitis is inflammation involving the lacrimal sac due to obstruction of the nasolacrimal duct. In this disease, it has a characteristic clinical manifestation according to the course of acute or chronic disease such as epiphora and the appearance of signs of inflammation. This disease is more dominant in infecting women than men with a percentage of 77-100%: 0-20% and is also more common in patients aged 40 years and over. The method used in this journal is a literature review with the aim of knowing more about comprehensive management of dacryocystitis. This disease can cause complications in the tissues around the eyes if not treated properly, such as cellulitis, keratitis, and endophthalmitis. In preventing the occurrence of ongoing complications, dacryocystitis patients can be given warm compresses and the use of antibiotics erythromycin, clindamycin as a pharmacological therapy. Definitive therapy applied to this disease can be in the form of dacryocystorhinostomy (DCR) which has 2 approaches.